Severe acute hepatitis and acute liver failure of unknown origin in children: a questionnaire-based study within 34 paediatric liver centres in 22 European countries and Israel, April 2022 - Kleine, Ruben H. de; Lexmond, Willem S.; Buescher, Gustav; Sturm, Ekkehard; Kelly, Deidre; Lohse, Ansgar W.; Lenz, Dominic; Jørgensen, Marianne Hørby (Eurosurveillance, 2022)
To detect potential concern about severe acute hepatitis in children, we conducted a survey among 50 ERN RARE-LIVER centres. By 26 April 2022, 34 centres, including 25 transplant centres, reported an estimated median of 3-5, 0-2 and 3-5 cases in 2021, 2020 and 2019 and a mean of 2 (range: 0-8) cases between January and April 2022 (mean in 10 large liver transplant centres: 3). Twelve centres reported suspicion of an increase, but no rise.
Article published on 12 May 2022
Gesehen am 08.07.2022